Facing disinformation in democratic backsliding: the role of courts in Brazil - Clara Iglesias Keller; Diego Werneck Arguelhes (VRÜ Verfassung in Recht und Übersee, 2024)
This paper examines how democratic institutions respond to disinformation when it is weaponized by elected officials for illiberal purposes. It focuses on the role of courts in countering disinformation in Brazil from 2018 to 2022, when the country experienced threats to democracy, marked by the use of disinformation to undermine electoral and judicial checks. In response, Brazil's High Courts took an array of measures against disinformation, including content removal, social media regulation, and criminal proceedings. While these actions were crucial in promoting democratic resilience, they also raised concerns about judicial aggrandizement and its implications. The paper discusses the tension between the courts' role in protecting democracy and their institutional limitations as well as the potential impact on the public perception of courts and freedom of expression, of having judges taking the leading role in fighting disinformation.
Keywords: 340